Peran Brand Equity dalam Memediasi Pengaruh Country of Origin Image Terhadap Customer Loyalty Handphone Samsung - Kusuma, Agung Wirahadi; Pramudana, Komang Agus Satria (E-Jurnal Manajemen, 2014)
ABSTRACT This study aimed to analyze the influence of country of origin image of brand equity, the influence brand equity of customer loyalty, the influence of country of origin image of customer loyalty, and the mediation role of brand equity on the influence of country of origin image of customer loyalty at Samsung mobile phone products in Denpasar. This kind of research is associative research which is discussing relation relationship of each variable. Taking sample is by purposive sampling that adding certain criterias which are considered to be representative of the population. The results showed that: First, country of origin image gives significant effect on customer loyalty. Second, brand equity gives significant effect on costumer loyalty. Third, country of origin image gives positive and significant effect on customer loyalty Fourth, Brand equity significantly influential in mediates the influence of country of origin image against a significant level of customer loyalty variable. Based on explanation and conclusion above, its suggested to Samsung to do sustainable innovation and add Korean culture inside Samsung’s product which is to increase costumer loyalty Keywords: country of origin image, brand equity, customer loyalty